2023
DOI: 10.1021/acs.macromol.3c00440
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Self-Assembly of ABC-Type Bottlebrush Copolymers

Abstract: We have performed dissipative particle dynamics simulations to study the self-assembly of ABC-type bottlebrush copolymers (BBCPs), one portion of whose backbone is grafted by pairs of A-blocks and the other portion is grafted by B/C-blocks in pairs, focusing on the effects of the number of A side chains, the length of B side chains relative to that of C side chains, and the rigidity of the backbone on the formation of hierarchical structures. A number of hierarchical structures with the superstructures formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…At a larger scale, the phase separation between PS and the PEO­(PTA)- co -PE cylinders resulted in the HCP superstructures. To our knowledge, this unique HPC- in -HPC was experimentally visualized for the first time and differed from the CYL- out -CYL structures previously reported in the neat (A- co -B)- b -C mGBCP self-assembly, where the A-cylinders were positioned within the continuous phase of superstructures and aligned either perpendicular to the surface of C-cylinders or radiating outward from each C-cylinder . The addition of PTAs into the PEO domains may render the HPC- in -HPC structure in a stable state (Figures S17–18), as detained by the strong interaction between PTA and PEO segments.…”
Section: Resultsmentioning
confidence: 61%
“…At a larger scale, the phase separation between PS and the PEO­(PTA)- co -PE cylinders resulted in the HCP superstructures. To our knowledge, this unique HPC- in -HPC was experimentally visualized for the first time and differed from the CYL- out -CYL structures previously reported in the neat (A- co -B)- b -C mGBCP self-assembly, where the A-cylinders were positioned within the continuous phase of superstructures and aligned either perpendicular to the surface of C-cylinders or radiating outward from each C-cylinder . The addition of PTAs into the PEO domains may render the HPC- in -HPC structure in a stable state (Figures S17–18), as detained by the strong interaction between PTA and PEO segments.…”
Section: Resultsmentioning
confidence: 61%
“…If the bridging block is acted by a bottlebrush architecture, the introduced rigidity will increase the fraction of bridging configuration drastically. Moreover, if a bottlebrush block is connected to a linear block of different chemical component, it will amplify the effect of spontaneous curvature toward the linear block due to their architectural asymmetry. , In fact, with the advances in the synthesis methods of bottlebrush polymers, novel bottlebrush architectures including dumbbell-shaped, cone-shaped, and block miktobrushes have been synthesized, providing highly designable architectures for the bottlebrush block copolymers. Recent experimental and simulation studies have shown that when the molecular parameters, such as grafting densities, side-chain lengths, and molecular shapes, are appropriately designed, kinds of structures including complex networked and hierarchical structures, can be obtained. With high degree in the designability of bottlebrush, more novel self-assembly structures may be obtained in the future. More specifically, if an architecture is designed to enable the various sophisticated mechanisms simultaneously, either AB-type or ABC-type block copolymers will exhibit more unpredictable self-assembly behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…There are some other important architectures that have attracted increasing attention but are rarely introduced into the purpose design of architectures, such as bottlebrush and cyclic block copolymers. For the bottlebrush block copolymers, one of the most appealing aspects is their ability to form ordered structures with domain size approaching hundreds of nanometers, which is hardly affordable for the conventional block copolymers, making them ideal for the fabrication of photonic crystals. , Many experimental and theoretical works have demonstrated that bottlebrush block copolymers exhibit unique self-assembly behaviors. One of the remarkable features influencing the self-assembly for the bottlebrush architecture lies in the rigidity of the backbone induced by the dense grafting of side chains. If the bridging block is acted by a bottlebrush architecture, the introduced rigidity will increase the fraction of bridging configuration drastically.…”
Section: Discussionmentioning
confidence: 99%
“…Because the morphologies are difficult to identify clearly from instantaneous configurations due to thermal fluctuations, we calculate the local concentration by taking the time average on the instantaneous configurations of bead positions within one short period where the morphology does not change notably, using the method proposed previously …”
Section: Model and Methodsmentioning
confidence: 99%